Designing of Genow Botanical Garden with Sustainable Architecture Approach - Barkoosaraei, Masoumeh Hassan Doost Asl; Moshiri, Shahriar (Journal of History Culture and Art Research, 2017)
Now a day, botanical gardens are considered as the most important and influential public green spaces in most countries of the world. These complexes on one hand have scientific and research applications in the fields of botany, gardening, conservation and plant ecology, and on the other hand they play an important role in public education and tourism. So it can be said that botanical gardens have been converted from merely research environments to multi-functional green spaces. The purpose of this study is designing the Botanical Gardens in Genow ecotourism region, located in of north of Bandar Abbas as a research-tourism complex that has been welcomed by citizens and tourists and respond to the various of their users. Selecting Genow region was due to its vicinity to the Protected Area and Reserve Biosphere of Genow (in terms of life value of diverse plants of protected area). In the process of designing the relevance of botanical garden with Genow echo tourist area, in performance dimension have been considered by the use of Persian garden pattern, and in terms of relationship with nature, with the benefit of recreational spaces and enjoyment of sustainable architecture components (green roofs, living walls the biological filter in the interior parts), that due to having these features will be considered by non-researcher tourists in Genow ecotourism region.